Alien Landscapes? - Jonathan Glover (Harvard University Press, 2014)
This book is about mental disorders: how to think about them and how well those of us outside can get a feel for what they are like from inside. Some dispute the boundaries of mental disorder. Is autism a disorder, or should it be seen as â€œneurodiversityâ€? Is antisocial personality disorder rightly named, or is it just ruthless amorality? Is addiction mental illness or just moral weakness? Is either medication or psychotherapy appropriate to ease the devastating grief of bereavement, or should we avoid medicalizing this normal human experience? When and how much do mental disorders impair agency and responsibility? When should acting under the influence of severe depression excuse someone from responsibility for what she does? What do some disorders do to a personâ€™s identity? When someone with schizophrenia shows unprovoked hostility and aggression, does that reflect him, or is it his illness? How should we draw boundaries here? How much is the original person still present in severe dementia?